Emerging COVID-19 infection An updated appraisal - Malik, Yashpal Singh; Ansari, Mohd Ikram; Sircar, Shubhankar; Tiwari, Ruchi; Mishri, Jyoti; Dhama, Kuldeep (Indian Farming, 2020)
Coronavirus is a global concern these days. The massive outbreaks due to the novel coronavirus disease named COVID-19 has led to its affirmation by the World Health Organization (WHO) as a pandemic situation. It became the first pandemic by any of the coronaviruses affecting humans or animals. The Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is responsible for COVID-19 leading to acute respiratory distress and substantial mortality in the absence of any effective therapeutic. The disease has spread over 150 countries affecting nearly 2,00,000 people with around 8,000 human deaths. The adoption of suitable public health preventive measures and strengthening medical facilities are the best options for managing the disease. In this article, information on coronavirus is provided with a few facts on virus and infection, risks and do’s and don’ts for an awareness campaign.